2022
DOI: 10.1021/acs.molpharmaceut.1c00879
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Responsive Disulfide Cyclic Peptides: A New Strategy for siRNA Delivery

Abstract: RNA interference (RNAi) is a powerful tool capable of targeting virtually any protein without time-consuming and expensive drug development studies. However, due to obstacles facing efficient and safe delivery, RNAi-based therapeutic approach remains a challenge. Herein, we have designed and synthesized a number of disulfide-constraining cyclic and hybrid peptides using tryptophan and arginine residues. Our hypothesis was that peptide structures would undergo reduction by intracellular glutathione (more abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Our previous studies showed that cyclic CPPs, [WR] 4 and [WR] 5 , with alternation of tryptophan (W) and arginine (R) residues, increased the cellular uptake of different compounds such as phosphopeptides, doxorubicin, ,,, paclitaxel, camptothecin, curcumin, , anti-HIV drugs, , gadolinium nanoparticles, selenium nanoparticles, gold nanoparticles, , and oligonucleotides. , Cyclic CPPs containing alternate W and R residues demonstrated improved cellular uptake delivery when compared to linear CPPs . Moreover, the uptake of both [WR] 4 and [WR] 5 was not dependent on the endocytosis pathway. , …”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that cyclic CPPs, [WR] 4 and [WR] 5 , with alternation of tryptophan (W) and arginine (R) residues, increased the cellular uptake of different compounds such as phosphopeptides, doxorubicin, ,,, paclitaxel, camptothecin, curcumin, , anti-HIV drugs, , gadolinium nanoparticles, selenium nanoparticles, gold nanoparticles, , and oligonucleotides. , Cyclic CPPs containing alternate W and R residues demonstrated improved cellular uptake delivery when compared to linear CPPs . Moreover, the uptake of both [WR] 4 and [WR] 5 was not dependent on the endocytosis pathway. , …”
Section: Introductionmentioning
confidence: 99%
“…Other chemical reagents and solvents were purchased from Millipore-Sigma (Milwaukee, WI, USA) and used without further purification. More details regarding the materials used in the present study have been previously described [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cellular uptake experiment was conducted on the breast cancer cell line MDA-MB-231. The detailed protocol is provided in our recently published manuscript [ 7 ]. Briefly, cells were seeded in each well of the 24-well plate (approximately 200,000 cells per well) and were allowed to settle in the incubator at 37 °C for 24 h. The peptide and siRNA complexes were made at N to P ratios of 20 and 40, where the final concentration of siRNA in each complex was 36 nM, and were allowed to incubate for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations